Albumin-based therapeutics capable of glutathione consumption and hydrogen peroxide generation for synergetic chemodynamic and chemotherapy of cancer - Yang, Guangbao (2022)
A nanoscale therapeutic system with good biocompatibility was facilely fabricated by the coassembly of human serum albumin and glucose oxidase (GOD), where the former was pretreated with metal ions through a chelating agent or the chemotherapeutic prodrug oxaliplatin (Oxa(IV)). Among different chelating metal ions used, Mn2+ ion was selected to produce hydroxyl radical (•OH) efficiently through Fenton-like reaction, while GOD loaded in the system was able to generate a large amount of hydrogen peroxide for promoting efficient conversion into highly toxic •OH. In the meanwhile, the conversion of the Oxa(IV) prodrug into chemotherapeutic Oxa(II) was beneficial for the consumption of glutathione, thereby enhancing the chemodynamic therapy (CDT) efficacy. Based on the combined chemotherapy and CDT, the treatment with this system leads to superior antitumor outcome.